Nursing care delivery : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Turitea Campus, Palmerston North, New Zealand - Hamilton, Charmaine Elizabeth (Massey University, 2001)
The delivery of safe, efficient and effective nursing care requires knowledgeable senior executives and nurses who collaborate, have the common and primary goal of meeting patient need, and a shared understanding of nursing care delivery. The aim of this research was to explicate executives' and nurses' understanding of nursing care delivery in the Crown Health Enterprise (CHE) setting. Between March and December 1997 61 executives or senior nurses from 18 CHEs participated in semi-structured interviews. The interview tapes were transcribed and biographical details and some data relating to organisational structure were summarised. The remaining data were analysed using content analysis. Seven themes were identified. Organisational structure was seen as a self-contained entity. Systems approaches were not used. Planned, systematic and ongoing evaluation of structural change and care delivery was not evident. The resource implications of proposed changes were not canvassed. Little was known about the nature of nursing work in the CHE. There was a desire for closer links between nursing practice and nursing education. The approach to nursing research was fragmented and ad hoc. The findings indicate an overall lack of knowledge about nursing care delivery and the nature of nursing work in the reformed health care environment. It is suggested that the primary reasons for this are the paucity of international and national research on these subjects and a fragmented approach to the management and development of nursing in New Zealand. The findings also suggest a lack of sophisticated resource management and evaluation expertise. To ensure the development of innovative nursing practice/care delivery models and systems that will meet New Zealanders present and future need for nursing care it is strongly recommended that priority be given to identifying the nature and scope of nursing work. It is also recommended that: An independent nursing research unit with a capacity to carry out national and longitudinal research in nursing is established. An independent national agency to oversee the management and development of nursing in New Zealand is established. The Ministry of Health commission a review of health management education.
Keywords: Nursing practice; New Zealand; Health management; Nursing care delivery; Organisational psychology; Fields of Research::320000 Medical and Health Sciences::321100 Nursing